Antiproliferative Effects of EGFR inhibitor Cetuximab and PARP Inhibitor Combination on Non-Small Cell Lung Cancer Cell Line A549 and Cervical Cancer Cell Line HeLa : Effects of Combination of EGFR inhibitor Cetuximab and PARP inhibitor - Çetin, İdil and Topçul, Mehmet (Cellular and Molecular Biology, 2022)
In this study, the efficacy of Cetuximab and Parp inhibitor (Parp 1 inhibitor) used in targeted therapies, alone or in combination, on non-small cell lung cancer cell line A549 and cervical cancer cell line HeLa cells were evaluated. For this purpose different cell kinetic parameters were used. Cell viability, mitotic index, BrdU labelling index and apoptotic index were evaluated in experiments. In single applications Cetuximab at concentrations ranging from 1 mg/ml to 10 mg/ml and Parp inhibitor at concentrations 5 µM -7 µM - 10 µM were applied. IC50 concentration of Cetuximab for A549 was 1 mg/ml, the IC50 concentration of Cetuximab for HeLa was 2 mg/ml, the IC50 concentration of Parp inhibitor for A549 was 5 µM, and the IC50 concentration of Parp inhibitor for HeLa was 7 µM. In both single and combinations, there was a significant decrease in cell viability, mitotic index, BrdU labelling index and there was a significant increase in apoptotic index. A comparison of cetuximab, PARPi and combination applications showed the superiority of combined applications over single applications in all cell kinetic parameters used.